Experiences of Medical Undergraduates about “Interactivity” in General Embryology Lecture Classes- A Cross Sectional Study (The Planet, 2022)
Background: Anatomy lecture classes of Bangladesh usually follow the traditional, didactic, teacher-centered strategies. It is often suggested that conventional lectures should be replaced by structured sessions with interactive components by preparing lesson plans targeting to design of interactive lectures. Objective: The purpose of the study was to analyze students’ learning experiences how they observe “Interactivity” in General Embryology lecture classes. Methods and materials: Two surveys were conducted on 232 undergraduates of two medical colleges of Bangladesh using a questionnaire designed by the researcher to analyze the experiences of the undergraduates regarding different aspects of “interactivity” of their General Embryology lecture classes. Results: The survey results of this study regarding the experiences of the medical undergraduates have shown that out of the 55 questions regarding “interactivity”, the Embryology lectures scored three (3) or more scores, out of four (4) in case of only two (2) of the questions. Two (2) or more was scored in case of eighteen (18) questions only. Conclusion: These results broadly suggest lower levels of “interactivity” regarding most aspects of the General Embryology lecture classes in the eyes of Bangladeshi medical undergraduates.
Keywords: Interactivity; learning materials; nonverbal elements